Efficacy of (18)F-FDG PET/CT in the evaluation of patients with recurrent cervical carcinoma - Mittra, Erik (2009)
PURPOSE: Only a limited number of studies have evaluated the efficacy of (18)F-FDG PET/CT for recurrent cervical carcinoma, which this study seeks to expand upon. METHODS: This is a retrospective study of 30 women with cervical carcinoma who had a surveillance PET/CT after initial therapy. Sensitivity, specificity, accuracy, positive predictive value, and negative predictive value were calculated using a 2×2 contingency table with pathology results (76%) or clinical follow-up (24%) as the gold standard. The Wilson score method was used to perform 95% confidence interval estimations. RESULTS: The sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of PET/CT for the detection of local recurrence at the primary site were 93, 93, 93, 86, and 96%, respectively. The same values for the detection of distant metastases were 96, 95, 95, 96, and 95%, respectively. Seventy-one percent of the scans performed in symptomatic patients showed true-positive findings. In comparison, 44% of scans performed in asymptomatic patients showed true-positive findings. But, all patients subsequently had a change in their management based on the PET/CT findings such that the effect was notable. The maximum standardized uptake value ranged from 5 to 28 (average: 13±7) in the primary site and 3 to 23 (average: 8±4) in metastases which were significantly different (p=0.04). CONCLUSION: This study demonstrates favorable efficacy of (18)F-FDG PET/CT for identification of residual/recurrent cervical cancer, as well as for localization of distant metastases.